2014
DOI: 10.1074/jbc.m114.565655
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Conservation in Biogenesis of β-Barrel Proteins Allows Mitochondria to Assemble a Functional Bacterial Trimeric Autotransporter Protein

Abstract: Background: ␤-Barrel proteins are found in the outer membrane of Gram-negative bacteria, mitochondria, and chloroplasts. Results: Mitochondria are able to assemble the bacterial trimeric autotransporter YadA in a functional form. Conclusion: The lipoproteins of the BAM machinery are not absolutely required for the biogenesis of autotransporter protein. Significance:The evolutionary link of mitochondria to bacteria allows the former to process even prokaryotic-specific proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…Despite the phylogenetic distance separating spirochetes and proteobacteria (22) and the dramatically different subunit compositions of their Bam complexes (36), TprC and TprI expressed in E. coli with signal sequences appear to fold properly within the OM and achieve their correct topology. This finding clearly demonstrates that the bipartite conformation is not dependent on expression of these proteins in a particular lipidic milieu and is consistent with other reports showing that Bam complexes can recognize and fold OMPs from distantly related organisms (108). It also establishes E. coli as a viable heterologous platform for fine topologic mapping of T. pallidum rare OMPs and genetically dissecting their structure-function relationships, objectives that syphilologists have been striving for since the beginning of the molecular era (109).…”
supporting
confidence: 74%
“…Despite the phylogenetic distance separating spirochetes and proteobacteria (22) and the dramatically different subunit compositions of their Bam complexes (36), TprC and TprI expressed in E. coli with signal sequences appear to fold properly within the OM and achieve their correct topology. This finding clearly demonstrates that the bipartite conformation is not dependent on expression of these proteins in a particular lipidic milieu and is consistent with other reports showing that Bam complexes can recognize and fold OMPs from distantly related organisms (108). It also establishes E. coli as a viable heterologous platform for fine topologic mapping of T. pallidum rare OMPs and genetically dissecting their structure-function relationships, objectives that syphilologists have been striving for since the beginning of the molecular era (109).…”
supporting
confidence: 74%
“…Sam35 and BamD share no obvious sequence homology but perform the same receptor-like function in binding unfolded substrates at the surface of the membrane into which those substrates are inserted (21,30); therefore, the conservation of the β-barrel assembly mechanism extends beyond the steps performed by BamA. Previous reports demonstrating that some mitochondrial β-barrels can be assembled in bacteria and that some bacterial OMPs can be assembled in mitochondria implied that the assembly complexes have similar substrate recognition mechanisms (40)(41)(42)(43), and structural studies (13)(14)(15)(44)(45)(46) suggested that BamD might recognize OMP substrates based on its homology to proteins that bind C-terminal peptides (e.g., a component of the mitochondrial translocase, Tom70; a peroxisomal protein receptor, PEX5; and a factor responsible for organizing Hsp chaperone proteins, Hop). Our results connect these observations and provide the underlying molecular basis for substrate recognition, which explains the reciprocity of β-barrel assembly between mitochondria and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Removement or replacement of the signal peptide of EspP, an autotransporter of Escherichia coli that owns a long signal peptide, with a generic signal peptide impaired the translocation of the passenger domain across the OM, highlighting the importance of these specific signal peptides in maintaining the passenger domain in a suitable state for translocation across the OM by preventing its misfolding (Szabady et al 2005). Noteworthy, many periplasmic chaperone or protease also involved in the translocation of the TAAs; bacterial periplasmic chaperone Skp enhances the proper assembly of trimeric autotransporter (Ulrich et al 2014), the chaperone protease DegP degrades the accumulated pre-TAAs in the periplasm caused by mutation, which is important for correct biogenesis of TAAs (Grosskinsky et al 2007). Interestingly, Iwan Grin et al recently found a small trimeric inner membrane lipoprotein with direct influence on the structural integrity of SadA in the periplasm, suggesting that there may exist additional periplasmic proteins that assist autotransport process (Grin et al 2014).…”
Section: The Translocation Process Of Taasmentioning
confidence: 98%